For-Profit Hospital Status and Carotid Artery Stent Utilization in US Hospitals Performing Carotid Revascularization. Issue 11 (November 2017) - Chandler, Justin V.; George, Benjamin P.; Kelly, Adam G.; Holloway, Robert G.
Abstract : Background and Purpose—: Carotid artery stenting may be an economically attractive procedure for hospitals and physicians. We sought to identify the association of hospital ownership (nonprofit versus for-profit) on carotid artery stenting (CAS) versus carotid endarterectomy utilization in US hospitals. Methods—: Using the Nationwide Inpatient Sample admissions for cerebrovascular disease from 2008 to 2011, we identified all private, nonfederal US hospitals performing at least 20 carotid revascularization procedures annually, including carotid artery stenting ( International Classification of Diseases -Ninth Revision 00.63) or carotid endarterectomy ( International Classification of Diseases -Ninth Revision 38.12). We used a multilevel multivariable logistic regression controlling for patient demographics, comorbidities, and hospital characteristics, to assess the effect of hospital ownership on CAS use. Results—: Across 723 hospitals (600 nonprofit, 123 for-profit), 66 731 carotid revascularization admissions were identified. Approximately 1 in 5 (n=11 641; 17.4%) revascularizations received CAS. The mean CAS rate among nonprofit hospitals was 17.5 per 100 revascularizations (median, 11.5; interquartile range, 5.2–24.5), and the mean CAS rate among for-profit hospitals was 24.2 per 100 revascularizations (median, 16.0; interquartile range, 6.7–33.3; P <0.001). Adjusting for patient and hospital characteristics, for-profit hospital designation was associated with greater odds of CAS (adjusted odds ratio, 1.45; 95% confidence interval, 1.07–1.98). Conclusions—: For-profit hospital ownership is associated with a higher rate of CAS compared to nonprofit hospitals in those receiving carotid revascularization. Further research is needed to understand the individual- and system-level factors driving this difference. Abstract : Supplemental Digital Content is available in the text.